2015
DOI: 10.1111/acel.12408
|View full text |Cite
|
Sign up to set email alerts
|

Predicting all‐cause mortality from basic physiology in the Framingham Heart Study

Abstract: SummaryUsing longitudinal data from a cohort of 1349 participants in the Framingham Heart Study, we show that as early as 28–38 years of age, almost 10% of variation in future lifespan can be predicted from simple clinical parameters. Specifically, we found diastolic and systolic blood pressure, blood glucose, weight, and body mass index (BMI) to be relevant to lifespan. These and similar parameters have been well‐characterized as risk factors in the relatively narrow context of cardiovascular disease and mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…A 2015 article in Aging Cell called, "Predicting All-Cause Mortality from Basic Physiology in the Framingham Heart Study," surveyed the standard classical risk factors for heart disease, including systolic blood pressure, blood sugar, body weight, body mass index, and cholesterol level and found that all of these markers are significant when considered at a single moment, but when they are summated and viewed over time they achieve a much higher correlation with the mortality statistics. 23 This supports the idea that it is not the individual risk factors at a given moment that are so significant as it is the cumulative hazard that all produced together. This is a novel scientific perspective.…”
Section: Editorialsupporting
confidence: 56%
“…A 2015 article in Aging Cell called, "Predicting All-Cause Mortality from Basic Physiology in the Framingham Heart Study," surveyed the standard classical risk factors for heart disease, including systolic blood pressure, blood sugar, body weight, body mass index, and cholesterol level and found that all of these markers are significant when considered at a single moment, but when they are summated and viewed over time they achieve a much higher correlation with the mortality statistics. 23 This supports the idea that it is not the individual risk factors at a given moment that are so significant as it is the cumulative hazard that all produced together. This is a novel scientific perspective.…”
Section: Editorialsupporting
confidence: 56%
“…The apparent discordance between the observed subtle functional defects and significant mortality may be explained by survivor (or survivorship) bias (44). Over half of the SIRT5KO TAC mice had already died at the 4-week post-TAC time point, making the surviving group of animals more homogeneous and the cause of future mortality more difficult to predict (45). Characterizing cardiac function at multiple early time points after the TAC procedure and/or stratifying mice based on cardiac function may be required to detect a marked defect in cardiac function in the SIRT5KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several large population studies have indicated that the higher the office BP, the higher the risk of stroke and coronary heart disease, sudden death, heart failure, peripheral artery disease, and end-stage renal disease. Although some studies suggest that BP has limited predictive value for total mortality after the age of 70 years, 46 large epidemiological studies have shown that the associations between BP and CVD events are observed in the majority of subjects aged over 80 years. 47 However, although for the general population the relationship with BP extends from high BP levels to relatively low values (110-115 mm Hg for SBP and 70-75 mm Hg for DBP), in older populations, these lower thresholds are variable depending on the age and functional status of the studied subjects.…”
Section: High Bp and Cardiovascular Complicationsmentioning
confidence: 99%